Application of the direct Lyapunov’s method to the investigation of integral sets - Ignatyev, A. O. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The concepts are defined of the stability, attraction, and asymptotic stability of the integral sets of systems of ordinary differential equations. With the use of the second method of Lyapunov, a number of theorems are proved concerning the stability of integral sets.